A co-produced self-management programme improves psychosocial outcomes for people living with depression. Issue 4 (14th December 2015) - Turner, Andy; Realpe, Alba X.; Wallace, Louise M.; Kosmala-Anderson, Joanna
Abstract : Purpose: – There is growing interest in self-management support for people living with mental health problems. The purpose of this paper is to describe the evaluation of a co-designed and co-delivered self-management programme (SMP) for people living with depression delivered as part of large scale National Health Service quality improvement programme, which was grounded in the principles of co-production. The authors investigated whether participants became more activated, were less psychologically distressed enjoyed better health status, and quality of life, and improved their self-management skills after attending the seven-week SMP. Design/methodology/approach: – The authors conducted a longitudinal study of 114 people living with depression who attended the SMP. Participants completed self-reported measures before attending the SMP and at six months follow up. Findings: – Patient activation significantly improved six months after the SMP (baseline M =49.6, SD=12.3, follow up M =57.2, SD=15.0, t (113)=4.83, p < 0.001; d =0.61). Participants' experience of depression symptoms as measured by the Patient Health Questionnaire-9 significantly reduced (baseline M =15.5, SD=6.8, follow up M =10.6, SD=6.9, t (106)=7.22, p < 0.001, d =−0.72). Participants' anxiety and depression as measured by the Hospital Anxiety Depression Scale also decreased significantly (baseline anxiety: M =13.1, SD=4.2, follow up M =10.2, SD=4.4, t (79)=6.29, p < 0.001, d =−0.69); (baseline depression: M =10.3, SD=4.6, follow up M =7.7, SD=4.5, t (79)=5.32, p < 0.001, d =−0.56). The authors also observed significant improvement in participants' health status (baseline M =0.5, SD=0.3, follow up M =0.6, SD=0.3, t (97)=−3.86, p < 0.001, d =0.33), and health-related quality of life (baseline M =45.4, SD=20.5, follow up M =60.8, SD=22.8, t (91)=−2.71, p =0.008, d =0.75). About 35 per cent of participant showed substantial improvements of self-management skills. Originality/value: – The co-produced depression SMP is innovative in a UK mental health setting. Improvements in activation, depression, anxiety, quality of life and self-management skills suggest that the SMP could make a useful contribution to the recovery services in mental health.